And why should I go to the museum? : the museum as a learning arena for the kindergarten : examples from Norway and Greece. - Dardanou, Maria (Universitetet i Tromsø, 2011)
This study presents the concepts in practice regarding museum as a learning arena for kindergarten children. Information was obtained by kindergarten teachers both in Norway and in Greece, through questionnaires. The findings indicated that kindergarten teachers in Norway and in Greece have a positive attitude towards museum use in relation to their National Curriculum for the kindergarten. Consequently, almost all the fields of the Norwegian and the Greek Curriculum for kindergarten can be connected with the museum uses, according to the research findings. The findings supported the literature, suggesting that kindergarten teachers’ acquired knowledge related to museum education affects their museum uses. Additionally, it was indicated that there is a connection between the awareness of kindergarten teachers regarding learning in a museum context and museum uses through designing and carrying out of their own programs for their kindergarten children inside the museum setting. Furthermore, the impacts on preschool children of their participation in museum educational programs are positive and related to the learning theories, according to both Norwegian and Greek kindergarten teachers. In order to investigate these concepts, the researcher used questionnaires distributed to kindergarden teachers in Greece (Athens) and Norway (Tromsø and Oslo) and which were analyzed quantitatively.